Avaliação hematológica e bioquímica sérica de cães portadores de parasitos intestinais do município de Lagoa Santa, Minas Gerais - Maria Clara Madureira de Lima Prado (2022)
Canine endoparasites represent a challenge for One Health due to the zoonotic character that some parasites can represent, especially for people who work directly with these animals, such as in a shelter environment. As resistance to pyrantel and benzimidazoles has already been documented in Ancylostoma caninum, the objective of the present research was to analyze the hematological, serum biochemical and parasitological profile of dogs from a condominium (study 1) and from a community shelter (NGO GAPA/Lagoa Santa ) from the municipality of Lagoa Santa/MG, with evaluations at the NGO before and after deworming the animals with pyrantel pamoate (study 2) and mebendazole (study 3). The most common parasites were Ancylostoma sp. (39%), Toxocara canis (3%) and Trichuris vulpis (6%). , respectively. Among the most common laboratory alterations, anemia stood out, observed in ~11%, eosinophilia in ~44% and thrombocytopenia, observed in 50% of the animals evaluated. In the conditions in which this experiment was carried out, there was not enough evidence to affirm cases of parasitic resistance in dogs treated with pyrantel and mebendazole, but the results draw attention to the importance of surveillance and a more cautious use of anthelmintic drugs in dogs, in addition to from the scenario that the population exposed to the risks of zoonoses does not always have access to knowledge about them, making health education programs necessary, with the participation of professionals related to health and environmental sanitation. Keywords: zoonoses, intestinal parasitosis, hematological and biochemical alterations, anthelmintic resistance